Nature's Calendar: Spring Check - phenological observations made by Citizen Scientists - Langvall, Ola; Bolmgren, Kjell; Swedish Botanical Association (Swedish University of Agricultural Sciences, 2025)
Nature's Calendar (www.naturenskalender.se, in Swedish only) is run by the Swedish National Phenology Network (SWE-NPN), a consortium of Swedish universities, governmental agencies and non-governmental organisations. The Swedish University of Agricultural Sciences (SLU) hosts the network and is part of the Climate program within the environmental monitoring and assessment activity branch of the university. The main task for the Nature's calendar is to collect observations of different spring and autumn signs appearing during the vegetation season. SWE-NPN is connected to the monitoring of the Swedish Environmental Objectives, mainly concerning the objective Reduced Climate Impact, but is also collaborating with networks in Europe (through the Pan-European Phenology database - PEP725) and internationally (through the International Society of Biometeorology).

Data about the nature's calendar is collected in two ways, the long-term environmental monitoring through "Calendars", where phenological observations are reported all through the year, and through "Checks", where phenology observations are reported during short-time campaigns, giving a snapshot of the phenological status at a certain time of the year. The long-term environmental monitoring is performed by citizen scientists and professional observers at research stations and like. Since 2015, a campaign called "Vårkollen" (i.e. "Spring Check") has also been run April 30 - May 1 every year. In the Spring Check, Citizen Scientist's have reported observations of how far the development of the flowering of Liverleaf, Colt's-foot, Wood Anemone, Goat Willow and Bird Cherry, and budburst of birch have progressed. All species has also been reported in the historical dataset mentioned below.

The Spring Check campain is performed by two SWE-NPN partners, SLU and the Swedish Botanical Association (SBF), where SLU provides the technical platform and data analyses and SBF produce folders and by hosting regional contacts for the press. The results are made available to the public by press releases directly after the campain is finished.

Aims
The aim of the Nature's Calendar is to collect phenological data from the first spring sign to the last autumn sign, to be able to offer nation-wide data to everyone interested, to facilitate research, environmental assessments, the evaluation of environmental goals, etc, to be better prepared to meet the effects of climate change. Observations reported to the Nature's Calendar can be compared to similar observations collected for more than 100 years ago (see the Swedish Historical Phenology Dataset in "Related Reseach Data"), to detect evidence of phenological shifts over time that can be connected to climate change.

The aim with the data collection of the Spring Check is to obtain nationwide data that can provide information to understand, track changes and predict effects of climate change on natural plants in Sweden by studying the progress of some species all over the country at one and the same date every year, and compare the current progress with what have been seen in historical records of the same plants.

The dataset includes one file with observation data (spring_check_2015-2024.csv), one PDF file (metadata_spring_check_2015-2024.pdf) with metadata that describes how the included parameters should be interpreted and lists of included species and phases, and one PDF file (Varkollen_folder_2024.pdf) which is the instruction given to the observers (in Swedish, only). The observation data file includes totally 69,668 observations.

Naturens kalender (www.naturenskalender.se) drivs av Svenska fenologinätverket, som är ett nätverk med flera universitet, myndigheter och föreningar. Sveriges lantbruksuniversitet (SLU) är nätverkets huvudman och ingår i universitetets miljöanalysverksamhet, tillhörande delprogrammet Klimat. Huvuduppgiften för Naturens kalender är att samla in observationer av vårtecken, hösttecken och annat i naturens kalender. Nätverkets verksamhet är i första hand kopplat till Sveriges miljökvalitetsmål Begränsad klimatpåverkan, men ingår även i europeiska (genom Pan-European Phenology database - PEP725) och intermationella (genom International Society of Biometeorology) samarbeten kring fenologisk forskning och miljöövervakning.

Data om naturens kalender samlas in på två olika sätt. Dels bedrivs en långsiktig miljöövervakning i form av ”kalendrar” där rapporter om fenologiska observationer samlas in över hela året, dels genomför vi korta ”kollar” där vi tar en ögonblicksbild av naturens kalender i landet vid en viss tidpunkt på året. Med början 2015 genomförs Vårkollen som en 2-dagars kampanj 30 april - 1 maj, där vi med hjälp av medborgarforskares observationer från hela landet får en "ögonblicksbild" av hur långt våren kommit vid den tidpunkten. I Vårkollen görs observationer av hur långt utvecklingen av blomning hos blåsippa, tussilago, vitsippa, sälg och hägg, samt lövsprickningen hos björk, vilka även förekommer i det historiska datasetet (se nedan).

Vårkollen genomförs av två partners i Svenska fenologinätverket, SLU och Svenska Botaniska Föreningen. SLU står för teknisk plattform och databearbetning, medan SBF står för informationsmaterial och regional medverkan genom sina lokalföreningar. Båda organisationerna bidrar med information till allmänheten via pressmeddelanden inför Vårkollen och med resultaten efteråt.

Motiv och syfte
Målet med Naturens kalender är att samla in data om allt från första vårtecken till sista hösttecken, så att vi kan erbjuda landsomfattande data till alla intresserade, för att underlätta forskning, miljömålsarbete och information, vilket kan göra oss bättre rustade att möta klimatförändringens effekter. Observationerna i Naturens kalender kan jämföras med motsvarande observationer som gjordes för över 100 år sedan (se Svenskt historiskt fenologidataset i "Relaterade forskningsdata"), för att upptäcka fenologiska förändringar över tid som kan bero på klimatförändringar.

Målet med Vårkollen är att bidra med landsomfattande data för att bättre kunna följa, förstå och förutse klimatförändringens effekter på vilda växter i Sverige genom att studera statusen över hela landet för de ingående arterna och faserna vid en och samma tidpunkt och jämföra dessa med historiska observationsdata för samma arter.

Datasetet innehåller en fil med observationsdata (spring_check_2015-2024.csv), en PDF-fil (metadata_spring_check_2015-2024.pdf) med metadata som beskriver ingående variabler och listor på ingående arter och faser, samt en PDF-fil (varkollen_folder_2024.pdf), som är den instruktion som de som rapporterar kan läsa. Observationsdatafilen innehåller totalt 69 668 observationer.
Naturens kalender: Vårkollen - fenologiska observationer av medborgarforskare
Keywords: PLANT PHENOLOGY; Species distribution; Arters utbredning; spring (season); spring; phenology; citizen science; Salix caprea; sälg; Betula pendula; vårtbjörk; Betula pubescens; glasbjörk; Tussilago farfara; hästhov; Bird Cherry; hägg; Hepatica nobilis; blåsippa; Anemone nemorosa; vitsippa; Bird sherry; Hägg; Wood anemone; Vitsippa; Spring sign; Vårtecken; Birch; Björk; citizen science; medborgarforskning; Goat willow; Sälg; Colt's foot; Tussilago; Liverleaf; Blåsippa; Climate Science; Klimatvetenskap; Environmental Sciences; Miljövetenskap; Ecology; Ekologi; Biota; Biologi och ekologi